2021
DOI: 10.3390/su13073677
|View full text |Cite
|
Sign up to set email alerts
|

New Classification Method to Evaluate Pollution Levels of Sewage Contaminated Lakes

Abstract: Monitoring water quality to minimize deterioration of a lake’s functionality is important, as several Indian lakes are exposed to sewage contamination. Public health laboratories, citizen scientists, and volunteers in developing nations often find it difficult to perform elaborate tests to monitor the water quality of freshwater systems. Developing a classification method to evaluate the pollution status of sewage-contaminated lakes using limited tests will expand environmental monitoring of freshwater systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The better water quality of the Yellow River Basin in Jiaozuo compared to that of the Haihe River Basin may be attributable to the greater number of water systems that travel through urban or agricultural areas in the Haihe River Basin. Pollutants discharged by urban production and living activities and non-point source contamination from agriculture degraded water quality [14,15,35]. The findings of the present study indicated that the water quality of the Dasha River system, Xin River system, and Mang River system was severely contaminated.…”
Section: Evaluation and Analysis Of Whole-area Water Quality In Jiaoz...mentioning
confidence: 65%
See 1 more Smart Citation
“…The better water quality of the Yellow River Basin in Jiaozuo compared to that of the Haihe River Basin may be attributable to the greater number of water systems that travel through urban or agricultural areas in the Haihe River Basin. Pollutants discharged by urban production and living activities and non-point source contamination from agriculture degraded water quality [14,15,35]. The findings of the present study indicated that the water quality of the Dasha River system, Xin River system, and Mang River system was severely contaminated.…”
Section: Evaluation and Analysis Of Whole-area Water Quality In Jiaoz...mentioning
confidence: 65%
“…Every year, more than 420 billion m 3 of sewage is released into rivers, lakes, and seas, contaminating 5.5 trillion m 3 of fresh water and accounting for more than 14% of the world's total runoff [14]. Every day, millions of tons of waste are deposited into rivers, lakes, and streams throughout the globe, and each liter of wastewater can pollute 8 liters of fresh water [15]. In the United States, processed food waste, metals, fertilizers, and pesticides pollute 40% of water basins, whereas only 5 out of 55 rivers have barely usable water in Europe [16].…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have recognized the local communities' involvement in data collection in several sectors including population dynamics of animal species [22][23][24], marine debris abundance in sanctuaries [25], assessment of soil characteristics in urban green spaces [26], and development of green infrastructure and urban green spaces [27]. Citizen science has been successfully applied for the creation of data sets and monitoring of water quality in river catchments [28], streams and lakes [29,30], and wetlands [31].…”
Section: Introductionmentioning
confidence: 99%